MODEL PENERAPAN APLIKASI “VIRTUAL TRADING” DALAM MENINGKATKAN MINAT INVESTASI MAHASISWA SEBAGAI INVESTOR PEMULA - Andi Runis Makkulau; Rusdiaman Rauf (Program Pascasarjana STIE Amkop Makassar, 2020)
The purpose of this research is to find out and analyze the ease of shares investing in the capital market through implementation of virtual trading application (simulation application) to the students as novice investors so that they have an understanding of the investment process, namely stock trading online detailed so it can increase student’s interest on investment. The subjects in this study were undergraduate management students. This research writing method used descriptive qualitative analysis techniques. Applied by creating a stock investment model using virtual trading (simulation) through the stockbit application so students can find out the application model in increasing their investment interest as a novice investor. The results showed that the virtual trading application (simulation) provides investment convenience for students as novice investors as the initial learning process of investing and stock trading. The use of this application is zero-risk so students can learn how to make a good investment plan before investing in real accounts. In addition, students can find out the benefits and risks that will be faced in the actual stock investment whether students become an investor or trader in the stock market. Future research is expected to be able to take a wider scope of investment by taking the real capital market investment analysis method, especially the investment method for students to generate maximum profits and minimize the investment risks that will be faced. Keywords: Virtual Application, Investing’s Interest